Bobot Karkas dan Bagian Karkas Ayam Petelur Jantan (Gallus gallus domesticus L.) Setelah Pemberian Tepung Daun Kelor (Moringa oleifera Lam.) Sebagai Imbuhan Pakan - Dwi Rahmawati; Muhammad Anwar Djaelani; Kasiyati Kasiyati; Sunarno Sunarno (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Consumption of meat as a source of animal protein has increased every year, especially the consumption of rooster. The increasing cost of poultry feed has made it difficult for breeders to produce roosters that have meat with high protein content. The cost of poultry feed can be minimized by the addition of herbal ingredients, one of which is the addition of leaf powder. Moringa oleifera leaf powder contains various kinds of amino acids and antioxidants that can be used as a supplement to additives feed. This study aimed to evaluate the effect of M. oleifera leaf powder on carcass weight rooster (Gallus gallus domesticus L.). Completely randomized design (CRD) used in this study consisted of 5 treatment groups with three replications, namely the control treatment group and the basal feed treatment group supplemented with Moringa leaf powder 1; 2; 3; and 4%. The feed used is the standard starter and finisher period rations formulated with Moringa leaf powder according to their respective concentrations. Parameters were measured during the seventh week when the rooster was 49 days old, which included: body weight, carcass weight, breast weight, and thigh weight. Based on the research conducted, it was found that giving Moringa leaf powder 1; 2; 3; and 4% as feed additives in rooster had no significant effect (p> 0.05) on body weight, carcass weight, breast weight, and thigh weight. Overall, the conclusion of this study is the addition of Moringa leaf powder with a concentration of 1; 2; 3; and 4% in rooster feed up to 7 weeks of age did not affect on carcass weight, breast weight, and thigh weight of rooster.